Comparison of the Effects of Video Modeling and Clinician Modeling on Naming Deficiency in Aphasic Patients: - Kaviani, Shohre; Samaei, Afshin; Shahverdi, Ehsan; Kasbi, Fatemeh (Galen Medical Journal, 2019)
Background: Â Aphasia is the most frequent disorder that could occur following a stroke. Aphasia has a negative impact on the patient’s communication ability through language. One of the common consequences of aphasia is naming deficits that can lead to communication disorders. Therefore, the treatment of aphasia is necessary. The aim of the current study was to investigate the effect of video modeling and clinician modeling on naming skills of patients with chronic aphasia.Materials and Methods: The design of this prospective single subject study was Aâ€‘Bâ€‘A that performed on four patients with chronic aphasia. participated. This study was administered during three phases including the baseline (three sessions); the intervention (nine sessions); and a follow-up phase (three sessions). The outcome measure was taken in three phases including baseline, intervention, and follow-up. For each patient, the naming score for items modeled by the clinician, the naming score for items modeled video modeling by other, the naming score for self-video modeling, and the reaction time score were recorded.Result: A total of three patients complete the study and one of them refused to continue treatment. The naming score of all modeling types increased in all patients. In the other words, the intervention helped the patients be improved in naming. Also, the results of the reaction time indicated that the video modeling, as well as clinician modeling, could decrease the response time that means the intervention could increase the speed of retrieval processes.Â Conclusion:In our study, all three types of modeling could improve the naming scores in patients with chronic aphasia. Additionally, the findings demonstrate that the clinician and video modeling might increase mental processing for naming verbally. [GMJ. 2019;8:e1158]